Remaking global order : the evolution of Europe-China relations and its implications for East Asia and the United States - Casarini, Nicola, 1971- (Oxford : Oxford University Press, 2009)
This title offers an examination of the evolution of contemporary EU-China relations in the economic, technological and high politics dimensions, including implications of the high-tech and security-related elements of this relationship.
Includes bibliographical references and index.
Description based on print version record.
Keywords: European Union countries -- Foreign relations -- China; China -- Foreign relations -- European Union countries; United States -- Foreign relations; East Asia -- Foreign relations